The evolution of religion, religiosity, and theology
1 online resource
Keywords: "This book takes a multi-dimensional and multi-disciplinary approach to religion, religiosity and theology from their earliest beginnings to the present day. It uniquely brings together the natural sciences and theology to explore how religious practice emerged and developed through the four sections into which the book is organized: Evolutionary biology; Philosophical linguistics, psychology and neuroscience; Theology and Anthropology. The volume features an international panel of contributors who develop an innovative picture of religion as a culturally-created social institution; religiosity as a more personal and subjective anthropological element of people expressed through religion; and theology as the study of god. To survive in changing times, living systems - a good characterization of religion, religiosity and theology - all must adaptively evolve. This is a vital study of a rapidly burgeoning field. As such, it will be of great interest to scholars in religious studies and theology as well as in the psychological, sociological, and anthropological study of religion"--